Takhrij Hadits Berbasis Android: Ilustrasi tentang Doa Iftitah - Syahputra, Muhammad Ryan (SHAHIH (Jurnal Ilmu Kewahyuan), 2023)
This article attempts to contain the steps for using the Android-based "Takhrij Hadith" application. With the advancements that humans enjoy in this modern age, humans can find various conveniences. The Prophet's hadiths were also not spared. If we look at it historically, in the period before the discovery of several technological advances, such as today, our hadith scholars made various efforts to carry out research related to the mentakhrij of a hadith. And that requires quite a bit of time. Considering the many hadith sources that must be researched in order to interpret a hadith. The findings of this research are that the method of mentahrij hadith prayer iftitah, namely the prayer Allahu akbar kabiraa. However, now the author carries out the activities of takhjir hadith prayers above using applications available on Playstore (which is available on Android). The first step that a researcher must prepare for is the availability of a supported smartphone in his hand. Then after that the researcher can download the takhrij hadith application which is available on Playstore